Functionally Guided Precise Synthesis of Manganous Oxide‐Polyoxometalate 2D Hybrid Sub‐1 nm Nanosheet Superstructures. Issue 7 (21st April 2022) - Liu, Junli; Shi, Wenxiong; Nie, Siyang; Wang, Xun
Abstract : The 2D hybrid sub‐1 nm nanomaterials (HSNMs) hold great promise in catalysis due to the large surface areas giving rise to more catalytic centers exposed and the possible synergetic effect of multiple components. It is a useful strategy to fabricate the highly active and selective 2D HSNMs catalysts by combining inorganic compound with polyoxometalates (POMs) at the sub‐1 nm scale, since POMs are usually easier to accept or lose electrons, which possibly regulate the valence state of inorganic component leading to the enhanced catalytic properties. Inspired by this, from a function‐oriented perspective, three sorts of MnO‐POMs 2D hybrid sub‐1 nm nanosheets (HSNSs) are successfully prepared, which perform outstanding catalytic activity and selectivity in the chemoselective C–H oxidation of alcohols to aldehydes. Molecular dynamic (MD) simulations study the formation mechanism of the 2D HSNSs, and density‐functional theory (DFT) calculations prove the introduced POMs slightly oxidize Mn 2+, thus improving the oxidizability of MnO in the oxidation of alcohols to aldehydes. Herein, a new idea for the functionally guided inorganic precise synthesis of 2D sub‐1 nm nanomaterials is provided. Abstract : Herein, three kinds of 2D hybrid sub‐1 nm nanosheets are constructed by introducing three sorts of polyoxometalates into MnO, respectively, which perform excellent catalytic activity and selectivity in the oxidation of alcohols to aldehydes. Molecular dynamic simulations and density‐functional theory are used to investigate the formation mechanism of materials and the reaction mechanism about the oxidation of alcohols, respectively.